2017
DOI: 10.1039/c7ta08993g
|View full text |Cite
|
Sign up to set email alerts
|

Photocorrosion-resistant Sb2Se3photocathodes with earth abundant MoSxhydrogen evolution catalyst

Abstract: A highly efficient Sb2Se3photocathode is resistant to photocorrosion in strongly acidic media without protective overlayers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 21 publications
9
100
0
Order By: Relevance
“…In addition, Figure S9b (Supporting Information) shows a minor broad band at 300-450 cm −1 corresponding to an amorphous phase of Sb 2 O 3 , [43] which can be formed along with the surface decomposition of Sb 2 Se 3 (Equation (2)). [44] Furthermore, a periodically varying potential sweep is unlikely to cause significant charge accumulation. Although Prabhakar et al proposed that Sb 2 Se 3 is intrinsically resistive to photocorrosion even in strong acidic media, they only focused on the potential region above 0 V RHE using cyclic voltammetry, where photocorrosion current was insignificant (<0.1 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Figure S9b (Supporting Information) shows a minor broad band at 300-450 cm −1 corresponding to an amorphous phase of Sb 2 O 3 , [43] which can be formed along with the surface decomposition of Sb 2 Se 3 (Equation (2)). [44] Furthermore, a periodically varying potential sweep is unlikely to cause significant charge accumulation. Although Prabhakar et al proposed that Sb 2 Se 3 is intrinsically resistive to photocorrosion even in strong acidic media, they only focused on the potential region above 0 V RHE using cyclic voltammetry, where photocorrosion current was insignificant (<0.1 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[63] However, the efficiency (in particular, the photovoltage) must be improved if it is to become truly practical. Antimony selenide (Sb 2 Se 3 ) is a promising photocathode candidate, as it can be easily fabricated by an electrodeposition/selenization process; it gives high photocurrents and is stable in 1 m H 2 SO 4 under illumination.…”
Section: Discussionmentioning
confidence: 99%
“…[73] Tungsten diselenide (WSe 2 ) has excellent optoelectronic properties as a single crystal, [74] and Yu et al have recently investigated this material as 2D exfoliated sheets, with hydrogen evolving photocurrents up to 4 mA cm −2 being achieved with this solution-processed material. [63] If the photovoltage of this material can be improved, it is a strong candidate for a high efficiency, stable, and scalable water splitting photocathode. [76] Prabhakar et al demonstrated that thin-film Sb 2 Se 3 , a material previously investigated for water splitting with protective overlayers, [34,35] is actually stable toward corrosion in harsh acidic conditions under full sun illumination without protective layers, and generates high hydrogen-evolving photocurrents when coupled with an amorphous MoS x layer (Figure 4).…”
Section: Photocathode Materials Without Corrosion Protection Layersmentioning
confidence: 99%
“…Recently, the solution‐processed Sb 2 Se 3 photocathodes achieved −11 mA cm −2 at 0 V versus reversible hydrogen electrode in the near‐neutral electrolytes . In a strongly acidic electrolyte (1 m H 2 SO 4 , pH ≈ 1), Sb 2 Se 3 thin film prepared with the selenization of electrodeposited Sb and Pt cocatalyst further improves the photocurrent density to 16 mA cm −2 at 0 V RHE . By introducing a Cu‐doped NiO x hole‐selective layer as an effective bottom contact layer for a solution‐processed Sb 2 Se 3 photocathode, a record photocurrent density of 17.5 mA cm −2 at 0 V RHE in acidic electrolytes is achieved …”
Section: Introductionmentioning
confidence: 99%
“…Although Sb 2 Se 3 photocathodes were reported as intrinsically stable toward photocorrosion in acidic electrolytes (pH ≈ 1), to achieve high stability, anti‐photocorrosion layers were widely applied . Among all the stable performances reported so far, Sb 2 Se 3 has been protected by precious metal cocatalysts such as Pt or RuO x and high bandgap oxides, e.g., TiO 2 , to avoid the inevitable photocorrosion .…”
Section: Introductionmentioning
confidence: 99%